1986
DOI: 10.1002/etc.5620050601
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of pyridine derivatives in soil suspensions

Abstract: Relationships between structure and biodegradability were evaluated for 28 pyridine derivatives in nutrient solutions inoculated with soil and incubated at 24°C. Compounds studied included pyridine; mono‐ and disubstituted pyridinecarboxylic acids; and hydroxy‐, chloro‐, amino‐and methylpyridines. Disappearance of the pyridine added was measured by UV spectrophotometry, and the ammonium released by cleavage of the pyridine ring was measured by colorimetry. Volatilization was estimated by analysis of the pyridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Experiments were conducted with batch cultures and soil suspensions, using various pyridine derivatives as substrates. These studies showed that pyridinecarboxylic acids had the highest transformation rate, followed by monohydroxypyridines, methylpyridines, aminopyridines, and chloropyridines (114,115). Carboxyl substituents at any position of the pyridine ring stimulated decomposition more than did any other substituent, whereas chlorosubstituted pyridines showed the lowest degradation rate (76).…”
Section: Comparative Transformation Rates Of Pyridine Derivativesmentioning
confidence: 99%
“…Experiments were conducted with batch cultures and soil suspensions, using various pyridine derivatives as substrates. These studies showed that pyridinecarboxylic acids had the highest transformation rate, followed by monohydroxypyridines, methylpyridines, aminopyridines, and chloropyridines (114,115). Carboxyl substituents at any position of the pyridine ring stimulated decomposition more than did any other substituent, whereas chlorosubstituted pyridines showed the lowest degradation rate (76).…”
Section: Comparative Transformation Rates Of Pyridine Derivativesmentioning
confidence: 99%
“…The maximum charge qql that can be acquired by a particle in aic by triboelectrification is glven by the Gaussian limit (Cross, 1987), that is, 2 _ qm = _dp _oEb (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or maximum charge-to-ma_s ratio…”
Section: Limit Of Charhs_b _ Trioboelectrificationmentioning
confidence: 99%
“…Thus, the removal of pyridine from wastewater is an important research topic worthy of detailed study. At present, many researchers have devoted themselves to develop effective and economical methods to deal with the wastewater containing pyridine and the common methods used for the removal of pyridine from wastewater mainly including photocatalysis (Zhao et al, 2004), membrane separation (Mandal and Bhattacharya, 2006), biological degradation (Lee et al, 1994;Rhee et al, 1996;Sims and Sommers, 1986), ozonation (Andreozzi et al, 1991), and so on. However, these methods often involve complex process, high cost, and even may lead to secondary pollution during removal process.…”
Section: Introductionmentioning
confidence: 99%